Comparative fuel cell sustainability assessment with a novel approach. (1st January 2022) - Acar, Canan; Beskese, Ahmet; Temur, Gul Tekin
Abstract: Fuel cells have been attracting many researchers and industry partners' attention due to their clean, quiet, modular, and flexible operation characteristics. As Power-to-Gas technologies evolve and get more sustainable, well-developed fuel cells will be needed to convert the chemical energy stored in the gas form to useful products such as power and heat. For that reason, a comprehensive sustainability investigation of fuel cells is conducted by taking their economic, environmental, social, and technical performance into account. The selected fuel cells are polymer electrolyte membrane, alkaline, phosphoric acid, molten carbonate, and solid oxide. These fuel cells' performance is comparatively investigated based on four primary and 15 sub-criteria. The selected performance criteria are economic (initial and running costs), environmental (GHG emissions, land use, solid waste generation, and water discharge quality), social (employment and training opportunities, impact on public health, and public acceptance), and technical (energy and exergy efficiencies, process control, start-up time, and scalability). This study is the first in the literature to conduct an in-detail and very inclusive sustainability evaluation of fuel cells. It is expected to guide many professionals from academia and industry towards developing cleaner, safer, more affordable, and efficient fuel cells. Highlights: A comprehensive sustainability investigation of fuel cells is conducted. The economic, environmental, social, and technical performance are taken into account. The selected fuel cells are PEMFC, AFC, PAFC, MCFC, and SOFC. The comparative sustainability performance is based on four primary and 15 sub-criteria. It is the first one in the literature with an in-detail and very inclusive sustainability evaluation of fuel cells.